Perbedaan Kadar Glutation (GSH) Hepar Tikus Putih Jantan (Rattus norvegicus) yang diinduksi Parasetamol Dosis Toksik dengan Pemberian Ekstrak Daun Kelor (Moringa oleifera) - Nur Insani; H.M.T Kamaluddin; Swanny Swanny (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Glutathione (GSH) transferase deficiency due to paracetamol exposure causes further oxidative stress to liver necrosis. To reduce oxidative stress that can cause damage to the liver of the body requires antioxidants. One plant to treat liver disease is the kelor leaf (because it has an active flavonoid material also has antioxidant activity). This study was conducted to determine the difference of glutathione hepar levels of male white rat induced paracetamol toxic dose by giving kelor leaf extract. The type of research is experimental laboratory in vivo with rancagan randomized post test only control group design. With the stages as follows 1.Leaf Extract Kelor with Ethanol 96%, 2.Perpeteration of experimental animals, 3.Treatment of experimental animals by giving extract of 3-dose of kelor leaf that is KP I 250 mg / 200 gr BB rat, KP II 500 mg / 200 gr BB rat, KP III 1000 mg / 200 gr BB rat  for 14 days combined with paracetamol dose 2 gr / 200 gr BB rat compared with the negative control group (group given only paracetamol dose 2 gr / 200 gr BB rat) and control group positif only fed regular feed for 14 days). The result showed that there was a significant difference mean of GSH levels between all treatment groups obtained p = 0,000 (p <α) p values smaller than 0.05. There was the highest increase of GSH in treatment group II (142,7525 μmol / mg) and lowest dose of GSH in positive control group (57,1812 μmol / mg), dose paracetamol toxic dosage and kelor leaf extract 500 mg / gr BB rat can increase GSH hepar p = 0,000 (p <α) p less than 0 , 05. The conclusion of the test results showed that giving of kelor leaf extract at dose of treatment group II can increase GSH hepar level significantly